Will the Economic Impact of COVID-19 Persist? : Prognosis from 21st Century Pandemics - Emmerling, Johannes (IMF Working Papers; Working Paper ;, 2021)
COVID-19 has had a disruptive economic impact in 2020, but how long its impact will persist remains unclear. We offer a prognosis based on an analysis of the effects of five previous major epidemics in this century. We find that these pandemics led to significant and persistent reductions in disposable income, along with increases in unemployment, income inequality and public debt-to-GDP ratios. Energy use and CO2 emissions dropped, but mostly because of the persistent decline in the level of economic activity rather than structural changes in the energy sector. Applying our empirical estimates to project the impact of COVID-19, we foresee significant scarring in economic performance and income distribution through 2025, which be associated with an increase in poverty of about 75 million people. Policy responses more effective than those in the past would be required to forestall these outcomes.